Transformational Leadership Dimensions and Its Role in the Rationalization of Banking Decisions: An Exploratory Esearch of the Views of A Sample of the Officials In the Iraqi Private Banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The current research aims to find out the role of transformational leadership in decision-making wise, to cope with the decline in some of the banking performance indicators as a result of the absence of the modern concept of the leadership of those so-called B (Transformational Leadership) and preventing benefit from the advantages in the banks, and I test the research on a sample of the Iraqi private banks through applied to a sample (77) Mdermvud and Associate Director and Advisor to the Chairman of the Department, the distributors (7) banks, and used the head of the questionnaire as a tool to collect data and information. For the purpose of access to the results, the research sought to test two hypotheses two main hypotheses sub pop them related to relations correlation and influence between the variables of research presidents, and for data processing, use some statistical methods (such as the arithmetic mean, standard deviation, percentages, correlation Spearman coefficient, simple regression coefficient ), and the adoption of a program (SPSS 20) the research found an association relations significantly between the two variables, and the presence of a significant effect of the dimensions of transformational leadership and keep making good in the surveyed banks, which demonstrates that the possible adoption of the dimensions of transformational leadership and interest in ousting the foundation actually, with proven desire of managers in the banks above the adoption of these dimensions in the future, and based on the findings, the research findings, it is recommended to benefit from the results and recommendations of the current research, particularly in the aspects of the dimensions of transformational leadership analysis of the form in which they can make the most of the indicators generated, it is essential to the surveyed banks that based on scientific concepts in the selection and testing of the leadership process, and that these leaders have the ability to think big, creativity and thus make rational decisions.